Prevalence of impacts of dental and oral disorders and their effects on eating among older people; a national survey in Great Britain - Sheiham A, Steele JG, Marcenes W, Tsakos G, Finch S, Walls AWG (Blackwell Synergy, 2001)
The objective was to assess the prevalence, in a British population aged 65 years and older, of oral health related impacts and the effects they had on the quality of daily life and in particular on eating.